Field Detection and Numerical Simulation Study on Roof Asymmetric Fracture Mechanism of Large-Span Soft Rock Roadway with Discontinuity Surface - Liang Chen; Shouyang Gao; Bin Miao; Nan Yao; Shizhong Zhang; Wei Zhang (Geofluids)
Existence of roof discontinuity surface is one of the extremely important factors causing the asymmetric fracture of roadway roof, especially for large-span soft rock roadway. In this paper, a crack density coefficient (D) is firstly defined by local thresholding-microcell segmentation method and used to analyze the evolution law of D with roof drilling depth (d) (the lower and upper of roof discontinuity are defined as regions I and II, respectively). Then, UDEC numerical simulation is used to investigate the asymmetry evolution law of roof total displacement, maximum principal stress, and crack density with stress release coefficient (α) considering the effect of discontinuity surface. Research results indicate that (1) the roof parameters (D) in regions I and II both show a negative logarithmic function decreasing trend with the increase of drilling depth. When d<4.5 m, the parameter (D) in region II is about 1.5 times that in region I; when d≥4.5 m, the parameter (D) in region I is almost zero, while the parameter (D) in region II maintains a slight decreasing trend. Roof failure presents asymmetric distribution characteristics along both sides of the discontinuous surface. (2) In the initial stage of open-off cutting excavation, the top left and right corners of roof as well as the bottom of discontinuous surface first occurred the tension-shear failure, and then as the α increases, the two side cracks gradually shift to the middle of roof in regions I and II with the appearance of stress concentration in two top corners. Meanwhile, the direction of maximum principal stress is transformed from “direction approximately parallel to the excavation surface” to “direction perpendicular to the discontinuous surface,” of which the location transfers to the deep anisotropically, forming an asymmetric stress loosening zones in the roof of regions I and II. The range of stress loosening zone in region II is significantly larger than that in region I. When the surrounding rock stress is completely released, the roof cracks in region I gradually transition from nonconnected to connected state and form a “quasi-right triangle” loosening zone. In addition, an “isosceles triangle-like” high crack density loosening zone with the roof middle as the axis is also formed in region II. The roadway roof presents a markedly asymmetric caving feature. (3) With the increase of discontinuity surface angles, the roof fracture range gradually decreases in region I and increases in region II as well as the structural features of roof pressure-bearing arch transform from “left-low right-high continuous asymmetric structure” (30°-60°) to “left-low right-high discontinuous asymmetric structure” (90°) to “unilateral partial pressure-bearing arch structure” (120°-150°). Research results can provide an extremely important reference for the optimization and design of support scheme with discontinuity-thick soft rock roof-large span roadways.